King of the stable - Carlson, Melody; Ellison, Chris (Wheaton, Ill. : Crossway Books, 1998)
While staying with his uncle, an innkeeper in Bethlehem, Matthew helps prepare a place for the baby Jesus to be born.
Keywords: Jesus Christ -- Nativity -- Juvenile fiction; Jesus Christ -- Nativity -- Fiction; Christmas -- Fiction; Jesus Christ; Nativity of Jesus Christ; Fiction; Juvenile works